Factors associated with differential T cell responses to antigens ESAT-6 and CFP-10 in pulmonary tuberculosis patients. Issue 8 (26th February 2021) - Liu, Shengsheng; Wu, Meiying; A, Ertai; Wu, Shucai; Geng, Shujun; Li, Zhihui; Li, Mingwu; Li, Liang; Pang, Yu; Kang, Wanli; Tang, Shenjie
Abstract : Abstract: The T-SPOT. TB assay detects cellular immune responses to 2 core Mycobacterium tuberculosis antigens, early secreted antigenic target of 6-kDa protein (ESAT-6) and culture filtrate protein-10 (CFP-10). T-SPOT. TB has been recently used for auxiliary diagnosis of active pulmonary tuberculosis (PTB). However, testing can produce inconsistent results due to differential PTB patient immune responses to these antigens, prompting us to identify factors underlying inconsistent results. Data were retrospectively analyzed from 1225 confirmed PTB patients who underwent T-SPOT. TB testing at 5 specialized tuberculosis hospitals in China between December 2012 and November 2015. Numbers of spot-forming cells (SFCs) reflecting T cell responses to ESAT-6 and CFP-10 antigens were recorded then analyzed via multivariable logistic regression to reveal factors underlying discordant T cell responses to these antigens. The agreement rate of 84.98% (82.85%–86.94%) between PTB patient ESAT-6 and CFP-10 responses demonstrated high concordance. Additionally, positivity rates were higher for ESAT-6 than for CFP-10 (84.8% vs 80.7%, P  < .001), with ESAT-6 and CFP-10 microwell SFC numbers for each single positive group not differing significantly ( P  > .99), while spot numbers of the single positive group were lower than numbers for the double positive group ( P  < .001). Elderly patients (aged ≥66 years) and patients receiving retreatment were most likely to have discordance results. ESAT-6 promoted significantly more positive T-SPOT. TB results than did CFP-10 in PTB patients. Advanced age and retreatment status were correlated with discordant ESAT-6 and CFP-10 results. Assessment of factors underlying discordance may lead to improved PTB diagnosis using T-SPOT. TB .